EQUIVALENT REPRESENTATIONS OF HIDDEN MARKOV MODELS - B. SETIAWATY (Dept. of Mathematics, IPB University, 2003)
In this article, we classify the class of hidden Markov models through the laws of the observation processes, since the Markov chains are not observable. Here, we also present some properties regarding this classiﬁcation.